The Effects of Religiosity, Trust, Intimacy Toward Commitment and Customer Loyalty at Shariah Microfinance - Rhamdhani, Intan Muliana; Riptiono, Sulis (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Customer loyalty is a crucial element of the goals achieved in every business. Companies must provide excellent service to increase customer loyalty. Thus, developing a theoretical model with empirical evidence related to customer loyalty to Islamic banks in Central Java is necessary. Self-administered questionnaires were used to collect the data. The study was conducted in Central Java by involving 230 shariah microfinance customers as respondents who were taken by purposive sampling. The data were analyzed using a structural equation model with AMOS (SEM-AMOS). The results of the study indicate that all hypotheses are accepted. Religiosity, trust, and customer intimacy can increase customer commitment and loyalty to services. Religiosity is a crucial antecedent that can increase commitment, while the variable that has the most considerable influence on increasing customer loyalty in shariah microfinance is customer commitment. Keywords: customer intimacy, loyalty, religiosity, shariah microfinance, trust